Information integration: needs and challenges - Skyrius, Rimvydas; Šimkonis, Saulius; Sirtautas, Indrius (Information & Media, 2015)
Information integration is one of the significant challenges for today’s business informatics to deal with. The development of a unified meaning out of multi-faceted information from assorted sources and formats is complicated by a number of technological, system and organizational challenges. The goal of this paper is to analyze the problems in the area of business information integration and propose practical recommendations for solving them. There are numerous approaches and technology platforms for information integration, unified by the goal to manage and unite the meaning contained in information, and it becomes evident that effective information integration has to be performed by a joint effort of users and technology. Different approaches are required for integration of structured and unstructured information – while the former requires the well-known tools and techniques of database domain, the latter requires much more flexible techniques, based on text analysis, text mining, fuzzy classification and intense participation of the users. It also has to be noted that forced integration of unstructured information using structured techniques creates a risk of stripping down the significant part of contained meanings. While dealing with information integration problems, a possible help would be the use of related experiences from the field of experience management or lessons learned.